2019
DOI: 10.1111/aos.14069
|View full text |Cite
|
Sign up to set email alerts
|

Does eye examination order for standard automated perimetry matter?

Abstract: Purpose In spite of faster examination procedures, visual field (VF) results are potentially influenced by fatigue. We use large‐scale VF data collected from clinics to test the hypothesis that perimetric fatigue effects are greater in the eye examined second. Methods Series of six Humphrey Swedish Interactive Testing Algorithm (SITA) VFs from 6901 patients were retrospectively extracted from a VF database from four different glaucoma clinics. Mean deviation (MD) was compared between first and second tested ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The limitation of this study was the absence of the consideration of some physical factors such as fatigue and loss of concentration, which may affect the results of reliability indices in that the eye tested second has a greater amount of variability [31][32][33]. However, these studies were based on older, prolonged examination protocols that are no longer used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The limitation of this study was the absence of the consideration of some physical factors such as fatigue and loss of concentration, which may affect the results of reliability indices in that the eye tested second has a greater amount of variability [31][32][33]. However, these studies were based on older, prolonged examination protocols that are no longer used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the 24-2C was tested after the 24-2 test, which may introduce a bias in the form of a fatigue effect. Kelly et al 45 found statistically significant reductions in mean deviation for the second eye tested resulting from fatigue, but this was unlikely to be clinically significant in magnitude. A prediction in this study would be that visual field indices would be systematically worse in the 24-2C.…”
Section: Clinical Impact Of 24-2c Exclusive Test Loca-tionsmentioning
confidence: 92%
“…Common considerations are the learning effect and between-eye fatigue effects. [42][43][44] Learning effects may manifest as greater rates of low test reliability in the eye that was tested first, with improvements seen for the second eye. The effect of fatigue in producing unreliable results have been widely reported in the second eye tested.…”
Section: Spes Can Be Detected Early In the Test Processmentioning
confidence: 99%